Enhancement of ferroelectricity in sputtered HZO thin films by catalytically generated atomic hydrogen treatment. (1st July 2022) - Mohit,; Wen, Yuli; Hara, Yuki; Migita, Shinji; Ota, Hiroyuki; Morita, Yukinori; Ohdaira, Keisuke; Tokumitsu, Eisuke
Abstract: Effects of catalytically generated atomic hydrogen (Cat-H) treatment on electrical properties of 10 nm thick sputtered hafnium-zirconium-oxide (HZO) films have been investigated. It is demonstrated that the Cat-H treatment to the as-deposited sputtered HZO film is effective to stabilize the metastable ferroelectric orthorhombic phase after crystallization. The enhancement of ferroelectricity by the Cat-H treatment is observed for the sputtered HZO films crystalized at a reduced pressure of 100 Pa, nitrogen and air, and the enhancement is pronounced for the films crystallized in nitrogen and air ambient. In addition, it is found that the Cat-H treatment also improves the stability against re-annealing.